Peranan Hukum Dalam Pembangunan Ekonomi Negara Menurut Pandangan Ibnu Khaldun - M Lohot Hasibuan (Al-Risalah, 2011)
The law is no longer a record of behaviors which shape the live of society; instead the law is expected to reveal the new powers which expect the properity of the society. As the result, almost all aspects of life are tied by law. The law should also realize that there are external factors which effect the law in the application in reality. In that way, when designing the law policy, the designer needs to condisioner some aspect such as psychology, sociology, and geografhy. Concerning on the development of national econ oconomy, ibnu khaldun stated that law should be based on religion rule for the reason that the law will organize the economic system well to be balance and develop the economic productivity.